How Does the FDA Evaluate AI in Combination Products? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
The integration of Artificial Intelligence (AI) into combination products, which merge a drug, device, and/or biological product, is rapidly transforming the...
Keywords: FDA Regulation and Compliance; Evaluate; Combination; Products; Artificial Intelligence; Machine Learning; Healthcare